Battery charger using wind turbine energy - Chen, Chi. (2011)
Nowadays, wind energy is more widely used as a solution to solve the problems caused by using of fossil fuels. Wind energy is converted to electrical energy by wind turbine. To meet the requirement of the daily use, the output of wind turbine is converted to different voltages and frequency. In this project, the output of wind turbine is converted to 440V. As the project is a simple model of the wind turbine charging system, all parts of the system are implemented by the basic design. This report starts from the introduction, and follows by the theories of each part of the system. The simulation schematic and simulation results are also include in the report. And the circuit and the results of experiment verify the design of wind turbine system. In this project, a wind turbine charging system with 440V output voltage is designed. To check whether the system works properly, simulation is done by PSIM firstly. The simulation result shows the design works well. Then hardware is built for the demonstration. Considering the safety and the limitation of the laboratory, the hardware has the 23V line to line rms input instead of 230V line to line rms voltage. And can get a 44V output as expect.